Perubahan Konsentrasi Kepemilikan Media PT Jawa Pos Holding - Amilia, Dinda Lisna; Fitranisa, Intan (Jurnal Riset Komunikasi (JURKOM), 2025)
PT Jawa Pos Holding is a major media company with a network across various provinces in Indonesia. In 2017, a conflict among shareholders led to Dahlan Iskan, the chairman, leaving the company. This situation impacted PT Jawa Pos Holding’s media landscape. This research explores the aftermath of Dahlan Iskan’s separation from the company. Using a qualitative approach with a case study method, it reveals a shift in media ownership concentration at PT Jawa Pos Holding, marked by the transfer of several media outlets to Dahlan Iskan’s Disway Daily. The need for Dahlan Iskan, still a reader magnet, drove this transfer, which occurred without significant conflict due to the fluid and non-structural patron - client relationship between PT Jawa Pos Holding and its media followers.